Doctors at war life and death in a field hospital - Rond, Mark de (The culture and politics of health care work, 2017)
Doctors at War is a candid account of a trauma surgical team based, for a tour of duty, at a field hospital in Helmand, Afghanistan. With stories that are at once comical and tragic, de Rond captures the surreal experience of being a doctor at war. He lifts the cover on a world rarely ever seen, let alone written about, and provides a poignant counterpoint to the archetypical, adrenaline-packed, macho tale of what it is like to go to war.